Magnetism and Low-Temperature Magnetocaloric Effect in Gd7(BO3)(PO4)2O6 Compound with Monoclinic Lattice - Lu Tian; Xuetong He; Zhiwen Shen; Xinqiang Gao; Zhaojun Mo (Applied Sciences)
The development of magnetic refrigerants with both low-field responsiveness and a large magnetic entropy change in the sub-Kelvin temperature range remains a critical challenge for advancing cryogenic technologies. This study focuses on the monoclinic compound Gd7(BO3)(PO4)2O6, in which high-density Gd3+ ions form magnetic frustrated structures within the bc-plane and stack along the a-axis direction. The combination of a high magnetic ion density and frustrated magnetic configuration enables the coexistence of a low magnetic transition temperature and excellent magnetocaloric effects. Magnetic susceptibility measurements reveal an antiferromagnetic-to-paramagnetic phase transition below 2 K. The maximum magnetic entropy change reaches 35.2 J kg−1 K−1 under a varying magnetic field of 0–7 T. This study highlights the potential of frustrated magnetic interactions in monoclinic lattices with a high Gd3+ content for achieving superior cryogenic magnetocaloric performance.